Bronchoscopy and Thermal Ablation: A Review Article - Aristides J. Armas Villalba; Bruce F. Sabath (MDPI AG, 2024)
Thermal ablative techniques are part of the armamentarium of interventional pulmonologists for the treatment of a diverse range of pathologies, but most importantly used in airway obstruction and airway bleeding. These techniques can be categorized based on their onset of action into rapid and delayed ablative methods. Understanding the nuances of each technique is essential, as most clinical scenarios demand a combination of modalities, commonly referred to as a "multi-modality approach". This comprehensive review aims to elucidate the fundamental principles of rapid ablative techniques, including laser therapy, argon plasma coagulation (APC), and electrocautery, along with the research that underpins their clinical application.